The effect of maternal diabetes on the Wnt-PCP pathway during embryogenesis as reflected in the developing mouse eye - Beatriz López-Escobar; David A. Cano; Anabel Rojas; Beatriz de Felipe; Francisco Palma; José A. Sánchez-Alcázar; Deborah Henderson; Patricia Ybot-González (The Company of Biologists, 2015)
Embryopathies that develop as a consequence of maternal diabetes have been studied intensely in both experimental and clinical scenarios. Accordingly, hyperglycaemia has been shown to downregulate the expression of elements in the non-canonical Wnt-PCP pathway, such as the Dishevelled-associated activator of morphogenesis 1 (Daam1) and Vangl2. Daam1 is a formin that is essential for actin polymerization and for cytoskeletal reorganization, and it is expressed strongly in certain organs during mouse development, including the eye, neural tube and heart. Daam1gt/gt and Daam1gt/+ embryos develop ocular defects (anophthalmia or microphthalmia) that are similar to those detected as a result of hyperglycaemia. Indeed, studying the effects of maternal diabetes on the Wnt-PCP pathway demonstrated that there was strong association with the Daam1 genotype, whereby the embryopathy observed in Daam1gt/+ mutant embryos of diabetic dams was more severe. There was evidence that embryonic exposure to glucose in vitro diminishes the expression of genes in the Wnt-PCP pathway, leading to altered cytoskeletal organization, cell shape and cell polarity in the optic vesicle. Hence, the Wnt-PCP pathway appears to influence cell morphology and cell polarity, events that drive the cellular movements required for optic vesicle formation and that, in turn, are required to maintain the fate determination. Here, we demonstrate that the Wnt-PCP pathway is involved in the early stages of mouse eye development and that it is altered by diabetes, provoking the ocular phenotype observed in the affected embryos.